Psychological Approach To Riskology - Dinorokhon Muminova; Muratova Zulhumor Jamolovna (Universitas Muhammadiyah Sidoarjo, 2022)
In modern riskology, a certain amount of research experience has been accumulated on risk issues. Therefore, first of all, it is necessary to classify theoretical approaches in order to determine the definitions of the main features of riskology. To do this, it is expedient to refer not only to the social, but also to the economic, cultural and statistical features of the studied phenomena